(untitled) (Experimental biology, 2021)
considers the current state of soil fertility of the most highly fertile soils in the world - mountain-forest black-brown soils of natural relict walnut-fruit forests (WFF) of the Kyrgyz Republic, which occupy the largest tracts of the same type of forests on the Earth and is included by the UN headquarters in the list of UNESCO world biosphere reserves, as an important World natural heritage of our planet, and they protect all components of the OPF biosphere from excessive anthropogenic load and natural degradation in the context of global climate change and represent a natural storehouse for the accumulation of clean water, is a region of widespread development of ecotourism, recreational networks of boarding houses and resorts, and make an invaluable contribution as a natural gene pool when introducing promising varieties of nut and fruit plants in the world into production.